2015
DOI: 10.1051/0004-6361/201526256
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the molecular chemistry and excitation in obscured luminous infrared galaxies

Abstract: Context. Extragalactic observations allow the study of molecular chemistry and excitation under physical conditions which may differ greatly from those found in the Milky Way. The compact, obscured nuclei (CON) of luminous infrared galaxies (LIRG) combine large molecular columns with intense infrared (IR), ultra-violet (UV), and X-radiation and represent ideal laboratories for the study of the chemistry of the interstellar medium (ISM) under extreme conditions. Aims. Our aim was to obtain for the first time a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 66 publications
(146 reference statements)
3
91
1
Order By: Relevance
“…Observations of HC 3 N in the vibrationally excited levels probe T vib = 350 K between vibrational levels with T ex = 35 K measured within the ground-vibrational state (Martín et al 2011). This is again quite similar to the excitation conditions measured in NGC 4418 (Costagliola & Aalto 2010;Sakamoto et al 2010), as has been noted by Costagliola et al (2015). A comprehensive explanation on the excitation of HCN vibrational levels was presented by Sakamoto et al (2010) for NGC 4418, which also applies to the conditions we observe in Arp 220.…”
Section: Hcn Excitation Of Vibrational Levelssupporting
confidence: 88%
See 1 more Smart Citation
“…Observations of HC 3 N in the vibrationally excited levels probe T vib = 350 K between vibrational levels with T ex = 35 K measured within the ground-vibrational state (Martín et al 2011). This is again quite similar to the excitation conditions measured in NGC 4418 (Costagliola & Aalto 2010;Sakamoto et al 2010), as has been noted by Costagliola et al (2015). A comprehensive explanation on the excitation of HCN vibrational levels was presented by Sakamoto et al (2010) for NGC 4418, which also applies to the conditions we observe in Arp 220.…”
Section: Hcn Excitation Of Vibrational Levelssupporting
confidence: 88%
“…Line contribution to the continuum emission has been shown to be a problem in Arp 220 (Martín et al 2011), where the spectra are confusion limited because of both the prolific molecular emission and broad line widths. This becomes even more of a problem at high frequency, as has also been observed toward the LIRG NGC 4418 (Costagliola et al 2015), and it hinders finding line-free spectral regions to extract continuum information. Although the spectral lines presented in this paper were observed in the upper sideband of the two setups, we used the continuum windows available in both bands to better account for the spectral index (α ∼ 3) at these frequencies.…”
Section: Observationsmentioning
confidence: 99%
“…The ALMA observations by Costagliola et al (2015) even reported the HC 3 N J = 32−31 rotational transition, and some of the vibrationally excited HC 3 N lines. The latest highresolution line surveys in a number of very nearby galaxies (Meier & Turner 2005 and Meier et al (2014Meier et al ( , 2015 show that the derived HC 3 N abundances (on ∼100 pc, approximately GMC scales) are approximately several 10 −10 (relative to H 2 ), which is approximately an order of magnitude lower than the abundance of HCN and some other molecules.…”
Section: Discussion: Hc 3 N In Galaxiesmentioning
confidence: 99%
“…In very recent line surveys of a small number of local active galaxies (AGN and/or starbursts, Aladro et al 2015;Costagliola et al 2015), several HC 3 N transitions in 3 mm band (HC 3 N J = 10−9, J = 11−10 and J = 12−11) were detected. The ALMA observations by Costagliola et al (2015) even reported the HC 3 N J = 32−31 rotational transition, and some of the vibrationally excited HC 3 N lines.…”
Section: Discussion: Hc 3 N In Galaxiesmentioning
confidence: 99%
“…The C 3 H 4 isomer methylacetylene (CH 3 CCH; IE = 10.36 eV) isomer has been detected in a few astronomical surveys toward SgrB2, PKS 1830-211, L1544, and tentatively in NCG 4418 (Belloche et al 2013;Muller et al 2014;Vastel et al 2014;Costagliola et al 2015). Methylacetylene and its isomer allene (H 2 CCCH 2 ; IE = 9.69 eV) have been reactants in attempts to untangle the chemistry taking place in Titanʼs atmosphere (Vakhtin et al 2001;Goulay et al 2007;Zhang et al 2009).…”
Section: N H 2nmentioning
confidence: 99%